Penggunaan Biopolimer Polikaprolakton Sebagai Matrik Herbisida Lepas Lambat Asam 2,4-Diklofenoksi Asetat - Akmal Djamaan; Yutra Noka; Netty Suharty (STIFARM Padang, 2013)
The study on 2,4-Dichlorophenoxyacetic acid (2,4-D) microencapsulation by solvent evaporation method using polycaprolactone (PCL) as a polimer has been done. The monitored of data how the effect release of substance active toward coated during 480 minutes. From the result of disolution gave rapid disolution of microcapsulation 2,4-D higher at formula 2 rather than formula 1 and 3. This show thickly upholstry of PCL have an effect on to release of substance active. Kinetics method release of substance active of microcapsule 2,4-D following order zero, first order and equation of Higuchi.